Investigation of HDTMA mediated sol gel synthesis of N-doped SnO2 nanoparticles: studies of their electrical and optical properties. (23rd February 2021) - Aslam, Madeeha; Mahmood, Tahira; Naeem, Abdul; Ali, Rahmat
ABSTRACT: In the present study, HDTMA-mediated synthesis of Nitrogen-doped tin oxide nanoparticles (N-doped SnO2 ) was carried out by sol gel route without using ammonia solution. HDTMA also acts as a nitrogen dopant. X ray diffractometry (XRD) confirmed tetragonal rutile crystal structure of SnO2 . Scanning electron microscopy (SEM) studies showed spherical morphology of N-doped SnO2 . UV–Vis absorption spectroscopy of N-doped SnO2 showed an absorption edge at 310 nm and band gap energy was calculated to be 4.4 eV, indicating a clear blue shift due to quantum confinement of nanoparticles. PL emission spectra showed broad UV band peaking at about 335 nm, indicating a blue shift due to the reduction of particle-size and widening of the band gap. Electrical parameters such as dielectric constant, dielectric loss and Ac conductivity were studied in detail.